Bunge la kwanza katika mfumo wa vyama vingi vya siasa Tanzania, 1995-2000 - Msekwa, Pius (DUP (1996), 2000)
A collection of essays by the author, written between 1995 and 2000 as part of a civic education programme to explain the roles and functioning of parliament in a multi-party democracy. The author's aim was to create a better understanding among politicians, politcal scientists, and other observers of Tanzania's transition to political pluralism.